An exploration into first generation adult student adaptation to college - Schmidt, Carolyn Speer (Kansas State University, 2005)
The purpose of this study was to further develop an understanding of the nature of the adaptation process of adult first generation students to the undergraduate college experience. This study utilized the Student Adaptation to College Questionnaire (SACQ) in conjunction with personal interviews to explore whether first generation adult college students adapt differently to college than do their continuing generation peers and if there is a commonality of experience, across demographic differences, for first generation, adult college students. Fifty-five adult college freshmen were surveyed using the SACQ. From this sample, sixteen first generation volunteers were interviewed regarding their college experience. T-test analysis of the SACQ scores showed that the first generation students were not adjusting to college as well as their continuing generation peers on the overall measure to adjustment and on three of the four subscales. The personal interviews indicated that while there was variation in the first generation students’ adaptation with seven of the sixteen volunteers classified as adjusting poorly to college, three with mixed adjustment, and five with good adjustment, there were also commonalities in the students’ experience, regardless how well they were adjusting to college. Eleven meta themes emerged from the interview data, and these themes correlated with characteristics of nonpersisters as compiled by Kasworm, Polson, and Fishback (2002). This research indicated that further investigation into adult first generation college students is appropriate especially with regard to how these adults view themselves as role models. In addition, this study indicates a need for future research into the links between adult students’ first generation status and persistence problems in their college experience.
Keywords: First generation; Adult; Adaptation; Adjustment; College; Student Adaptation to College Questionnaire; Education, Adult and Continuing (0516); Education, Higher (0745); Education, Sociology of (0340)